No alteration of Cyp3A4 activity after major hepatectomy in the early postoperative period – A prospective before-after study. (July 2020) - Jedamzik, J.; Mühlbacher, J.; Fitschek, F.; Schwarz, C.; Burhenne, J.; Asenbaum, U.; Kaczirek, K.; Mikus, G.
Abstract: Background: The impact of major liver resection (LR) on the detoxifying function of the remaining liver tissue as represented by CYP3A activity has yet to be assessed. Therefore, this study evaluates the changes in CYP3A activity between preoperative values and after liver resection. Material and methods: To determine CYP3A activity, midazolam (MDZ) was used as a marker substance, 3 μg were applied intravenously one day before surgery and on the 3rd day after surgery. Subsequently blood was withdrawn at 0, 0.25, 0.5, 1.0, 1.5, 2.0, 2.5, 3, 4 and 6 h post application of the study drug. Plasma MDZ and 1-OH-MDZ concentration was assessed using a LC-MS/MS method. Volumetric analysis of the resected liver was done by syngo.CT liver analysis software (Siemens Healthineers) using preoperative multidetector computed tomography. Results: N = 13 (8 male/5 female) patients were included in this study and received preoperative evaluation, 11 patients were studied also after liver resection. The mean age was 62 (±15.3) years with a mean BMI of 23.6 ± 4.8 kg/m 2 . No patient suffered from acute liver dysfunction postoperatively. None of the pharmacokinetic parameters assessed were significantly altered by liver resection. CYP3A activity over time was not significantly reduced by major liver resection. Conclusion: This study gives first time data on the impact of major liver resection on CYP3A activity. It was shown that MDZ clearance representing in vivo CYP3A activity is not altered by major liver resection. This suggests no dose adjustment of commonly applied drugs which are CYP3A substrates needs to be carried out. Highlights: Major hepatectomy does not alter the drug modifying capacity of the remaining liver. CYP3A activity preoperatively and on the third postoperative day does not differ significantly. Unchanged CYP3A activity suggests high safety of perioperative drug therapy.